2005
DOI: 10.1007/s00240-005-0510-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxalate exposure on Madin-Darby canine kidney cells in culture: renal prothrombin fragment-1 mRNA expression

Abstract: It has been suggested that renal tubular cell damage induced by oxalic acid, one of the components of urinary calculi, may be involved in a variety of ways in the development of urolithiasis. During our study on a calculus related protein, renal prothrombin fragment-1 (RPTF-1), we noted that this is an inflammation related substance that mediates an acute inflammatory reaction, one of the original roles of prothrombin. RPTF-1 is a part of prothrombin that is a coagulation factor known to be expressed in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Oxalate toxicity is mediated in part by activation of lipid signaling pathways, which in turn can disrupt mitochondrial function by increasing the production of reactive oxygen species such as O 2 ‐ , hydrogen peroxide, singlet oxygen and hydroxyl radicals. Reactive oxygen species mediate cell injury by modifying lipids, proteins, and DNA, and this can result in the promotion of calcium oxalate crystal formation 3,11,15 . Oxidative damage is therefore considered to play an important part in stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate toxicity is mediated in part by activation of lipid signaling pathways, which in turn can disrupt mitochondrial function by increasing the production of reactive oxygen species such as O 2 ‐ , hydrogen peroxide, singlet oxygen and hydroxyl radicals. Reactive oxygen species mediate cell injury by modifying lipids, proteins, and DNA, and this can result in the promotion of calcium oxalate crystal formation 3,11,15 . Oxidative damage is therefore considered to play an important part in stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Following renal tubular cell injury, cellular degradation produces numerous membrane vesicles which are nucleators of calcium crystals as supported by in vitro and in vivo studies [ 41 ]. Injured cells release substances like renal prothrombin fragment-1 or other anionic proteins which induce COM crystal agglomeration [ 68 ]. Reactive oxygen species is thought to be one of the factors involved in renal cell injury [ 69 ].…”
Section: Mechanisms Of Renal Stone Formationmentioning
confidence: 99%
“…Recent evidence revealed that the injury of renal tubular epithelial (HK‐2) cells is closely related to the early process in renal calculi formation. Previous studies showed that high concentrations of oxalic acid and calcium oxalate crystals led to the injury, apoptosis, and necrosis of HK‐2 cells . Oxidative stress and inflammation play pivotal roles in this process and has been considered as an important link to the formation of intrarenal crystals.…”
Section: Introductionmentioning
confidence: 99%